Produção de etanol utilizando melaço de cana-de-açúcar por Saccharomyces cerevisiae de características floculantes - Camargos, Cristiane Vieira (2019)
Currently Brazil is the second world's largest producer of ethanol, presenting a favorable position to present advantages in the technology of production, such as large cultivable areas and favorable climatic conditions. In addition, Brazil is the world's largest producer of sugarcane, which is the most efficient raw material known for the production of ethanol, being its production from sugarcane juice is a well-established process in the country. These factors together with the growing world demand for ethanol make Brazil highly competitive in its commercialization. Molasses, the main by-product of the sugar industry, has high concentrations of fermentable sugars, being therefore a potential raw material for the production of bioethanol. In order to reduce production costs, studies are promoted in the direction of finding yeasts and alternative processes that achieve high yields and productivities for alcoholic fermentation. The use of flocculent yeasts in the production of bioethanol allows the elimination of the centrifugation step, once these yeasts decant in the absence of fermentable sugars. Additionally, fermentation technology under high concentration of sugar, conducted in fed-batch, minimizes the effect of inhibition by substrate. The objective of this work was to study the conditions of fed-batch fermentation using a strain of Saccharomyces cerevisiae with flocculent characteristics in high concentrations of sugarcane molasses. A study of the fermentation and flocculation capacity of four flocculent strains was carried out, which resulted in the selection of the Saccharomyces cerevisiae C2/00 strain donated by the Center of Chemical, Biological and Agricultural Research (CPQBA). After the choice of the strain was determined its generation time using synthetic medium, obtaining a value equal to 1,071 h. It was evaluated the influence of supplementation with nutrients (KH2PO4, MgSO4∙7H2O, [NH4]2SO4 and yeast extract) in the batch fermentation of medium based on sugarcane molasses in different concentrations obtaining the highest efficiency (85.4%) using 30.0% v/v molasses solution without addiction of nutrients. It has also been verified that the addition of nutrients in the molasses based fermentation medium does not improve the efficiency of the process for molasses concentrations above 20.5% v/v. Aeration in the NG fermentation in fed-batch was studied as a way to improve the process, however aeration favored cell growth in detriment of ethanol production. Subsequently, three fermentations, HG and VHG, with molasses based feed with different concentrations of ART were evaluated. The total amount of ART added in the fermentations was 209, 222 and 250 g/L. Fermentation of 225 g/L of ART resulted in better efficiency (89.45%) with final concentration of ethanol of 104.4 g/L while fermentation of 209 g/L of ART showed higher productivity (2.98 g/(Lh)) among them. The maximum concentration of ethanol (P'max) that the yeast C2/00 was able to reach was determined, obtaining a value equal to 105.35 g/L. From the experimental data of the fermentation of 225 g/L a kinetic model was proposed, where its parameters were determined by means of the nonlinear adjustment of the data. The maximum specific growth rate was 0.555 h-1 with KS and KIS equal to 2.63 and 12.437 g/L, respectively. The results obtained with the experiments were relevant for HG fermentation with sugarcane molasses using flocculent strain. To increase the final ethanol concentration in the wine, other strategies must be adopted so that the yeast can withstand higher concentrations of ethanol.